Indium tin oxide coated D-shape fiber as saturable absorber for passively Q-switched erbium-doped fiber laser. (April 2020) - Nizamani, B.; Jafry, A.A.A.; Abdul Khudus, M.I.M.; Memon, F.A.; Shuhaimi, A.; Kasim, N.; Hanafi, E.; Yasin, M.; Harun, S.W.
Highlights: Q-switched Erbium-doped fiber laser with indium-tin-oxide (ITO) saturable absorber (SA). ITO was deposited onto D-shaped fiber using electron beam. The Q-switched pulses operates at 1566.4 nm with the highest repetition rate of 52.77 kHz. The pulse energy was 5.68 nJ at 96.4 mW pump power. Abstract: We demonstrated a Q-switched Erbium-doped fiber laser (EDFL) using indium-tin-oxide (ITO) deposited onto D-shape fiber as a saturable absorber (SA). The D-shaped fiber was prepared using polishing wheel technique while the ITO was deposited onto the polished surface using electron beam deposition technique to establish excellent evanescent field interaction between the material and light on the surface of the polished region. The SA device was deployed into EDFL ring cavity to generate Q-switched pulses operating at 1566.4 nm. It was able to initiate pulses as short as 2.3 µs with the highest repetition rate of 52.77 kHz. Stability of the SA is proven as it produced stable pulses within the pump power of 55.2–96.4 mW with signal to noise ratio of 58.6 dB. Q-switched EDFL generates pulses with the output power of 300 µW and pulse energy of 5.68 nJ at 96.4 mW pump power. Therefore, ITO deposited onto D-shape fiber can be deployed as SA in EDFL cavity for portable Q-switched laser source.